Management of Field Windbreaks - Bijay Tamang; Michael G. Andreu; Melissa H. Friedman; Donald L. Rockwood (EDIS)
FOR-288, a 6-page illustrated fact sheet by Bijay Tamang, Michael G. Andreu, Melissa H. Friedman, and Donald L. Rockwood, summarizes the most important management practices needing attention from the time the windbreak is planted to when it is replaced. Includes references. Published by the UF School of Forest Resources and Conservation, September 2009.